Possibilities of Implementing Emotional Education in the School Context - Dimitrijević, Dragana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The presence of different emotional states, their development and changes in emotional expression over the years raises the question of responsibility for the children’s emotional development. This question indicates the possibility and responsibilities of the school as an organized educational institution to fulfil its educational function in this area. The aim of this work is to analyse the school from the aspect of emotional education in order to point out the strengths and possibilities of the school to achieve the set goals and tasks in practice. The paper used the method of content analysis based on a sample of available theoretical and empirical research. The most important contribution of this paper is a detailed analysis of the concept of emotional education in school with separate goals, tasks, methods, and contents that are practically applicable and can be the basis of the implementation of emotional education in everyday school practice. The absence of a systemic solution for this aspect of educational activity indicates that the driver must be changes in the goals and priorities of educational work, bearing in mind the connection of students’ emotional states with cognitive development and academic achievement. In the end, the teacher, the student, and the teaching contents were singled out as the most important factors in the implementation of emotional education in school. School is an environment in which students experience different emotions depending on the circumstances, interpersonal relationships, and individual differences, but also the context in which emotional education is carried out. At the same time, school also affects the emotional development of children. Observing teaching as an integral and most organized part of school life, which is based on the interaction between teachers, students, and teaching content, we highlight teaching opportunities for encouraging children’s emotional development. Courses focused on linguistics, art, and social studies offer multiple possibilities of emotional experience with their content, while the possibilities of other teaching subjects can be highlighted by the application of experiential and cooperative work methods that will enable students to develop collaborative relationships, understanding of others, and tolerance in group work. Teachers have the main role in emotional education by creating a positive and stimulating environment and by using the possibilities of course content to increase students’ emotional competencies. Relationships with peers stand out in the context of creating a school as a safe and supportive environment where children can practice competencies in social relationships. Educational interventions should be aimed at all elements of emotional education, which would develop a conscious, independent, and responsible person who understands their feelings and the feelings of others, possesses interpersonal skills, and knows how to properly direct their behaviour.